A New Species of Mites of the Genus Bdella (Acari, Bdellidae) from Ukraine - Maslov, S.I.; Khaustov, A.A. (Вестник зоологии, 2013)
Bdella kuznetsovi Maslov et Khaustov, sp. n. is described from storm detritus of Black Sea and Sivash Gulf of the Sea of Azov, Ukraine. Описан Bdella kuznetsovi Maslov et Khaustov, sp. n., обнаруженный в штормовых выбросах Чёрного моря и залива Сиваш Азовского моря из Украины.